A randomized phase II trial of veliparib, radiotherapy, and temozolomide in patients with unmethylated MGMT glioblastoma: the VERTU study. Issue 10 (13th May 2021) - Sim, Hao-Wen; McDonald, Kerrie L; Lwin, Zarnie; Barnes, Elizabeth H; Rosenthal, Mark; Foote, Matthew C; Koh, Eng-Siew; Back, Michael; Wheeler, Helen; Sulman, Erik P; Buckland, Michael E; Fisher, Lauren; et al.
Abstract: Background: Temozolomide offers minimal benefit in patients with glioblastoma with unmethylated O 6 -methylguanine-DNA methyltransferase ( MGMT ) promoter status, hence, the need for novel therapies. This study evaluated whether veliparib, a brain-penetrant poly(ADP-ribose) polymerase (PARP) inhibitor, acts synergistically with radiation and temozolomide. Methods: VERTU was a multicenter 2:1 randomized phase II trial in patients with newly diagnosed glioblastoma and MGMT -unmethylated promotor status. The experimental arm consisted of veliparib and radiotherapy, followed by adjuvant veliparib and temozolomide. The standard arm consisted of concurrent temozolomide and radiotherapy, followed by adjuvant temozolomide. The primary objective was to extend the progression-free survival rate at six months (PFS-6m) in the experimental arm. Results: A total of 125 participants were enrolled, with 84 in the experimental arm and 41 in the standard arm. The median age was 61 years, 70% were male, 59% had Eastern Cooperative Oncology Group (ECOG) performance status of 0, and 87% underwent macroscopic resection. PFS-6m was 46% (95% confidence interval [CI]: 36%-57%) in the experimental arm and 31% (95% CI: 18%-46%) in the standard arm. Median overall survival was 12.7 months (95% CI: 11.4-14.5 months) in the experimental arm and 12.8 months (95% CI: 9.5-15.8 months) in the standard arm. The most common grade 3-4 adverse events were thrombocytopenia and neutropenia, with no new safety signals. Conclusion: The veliparib-containing regimen was feasible and well tolerated. However, there was insufficient evidence of clinical benefit in this population. Further information from correlative translational work and other trials of PARP inhibitors in glioblastoma are still awaited.